Soluble CD73 in Critically Ill Septic Patients Data from the Prospective FINNAKI Study - Vaara ST; Hollmen M; Korhonen AM; Maksimow M; Ala-Kokko T; Salmi M; Jalkanen S; Pettila V (PUBLIC LIBRARY SCIENCE, 2022)
Background CD73 dephosphorylates adenosine monophosphate to adenosine that is an anti-inflammatory molecule inhibiting immune activation and vascular leakage. Therefore, CD73 could be an interesting mediator both in sepsis and acute kidney injury (AKI). We aimed to explore the soluble CD73 (sCD73) levels and their evolution in critically ill patients with severe sepsis and, second, to scrutinize the potential association of sCD73 levels with AKI and 90-day mortality.Methods This was a post-hoc laboratory analysis of the prospective, observational FINNAKI study conducted in 17 Finnish ICU during 5 months in 2011-2012. Plasma samples of 588 patients admitted with severe sepsis/shock or with developing severe sepsis were analyzed at 0h (ICU admission) and 24h, and additionally, on day 3 or day 5 from a subset of the patients.Results The median [IQR] sCD73 levels at 0h were 5.11 [3.29-8.28] ng/mL and they decreased significantly from 0h to 4.14 [2.88-7.11] ng/mL at 24h, P<0.001. From 24h to Day 3 (n = 132) the sCD73 levels rose to 5.18 [2.98-8.83] ng/mL (P = 0.373) and from 24h to Day 5 (n = 224) to 5.52 [3.57-8.90] ng/mL (P<0.001). Patients with AKI had higher sCD73 values at 0h and at 24h compared to those without AKI. Non-survivors with severe sepsis, but not with septic shock, had higher CD73 levels at each time-point compared to survivors. After multivariable adjustments, sCD73 levels at 0h associated independently neither with the development of AKI nor 90-day mortality.Conclusions Compared to normal population, the sCD73 levels were generally low at 0h, showed a decrease to 24h, and later an increase by day 5. The sCD73 levels do not seem useful in predicting the development of AKI or 90-day mortality among patients with severe sepsis or shock.